Problem internetnih volitev - Kovačič, Matej (Teorija in praksa, 2008)
The paper analyses some doubts and arguments against the introduction of Internet elections in Slovenia. The introduction of Internet voting presents some new problems, especially in relation to voting by secret ballot and direct voting. One of the main problems with Internet voting is that it does not in itself guarantee voting by secret ballot. A special procedure for making votes anonymous must take place, but this opens up the problem of trust in relation to the technology and procedure used. Another problem is that the information and communications systems used to provide Internet elections are highly complex systems. Greater complexity results in a lower degree of transparency and a reduced level of security. Internet elections are not just another e-service or e-transaction because the security of Internet elections cannot be guaranteed using voter identification. Finally, the paper presents an analysis of the efficiency and reasonableness of introducing Internet elections. The results show that the introduction of Internet elections should not be undertaken too quickly and without proper debate and reflection.
Keywords: election; Elections; Volitve; Electronic voting; Elektronsko glasovanje; Informacijska tehnologija; Information technology; Information society; Informacijska družba; Data security; Varnost podatkov; e-volitve; informacijska varnost